2015
DOI: 10.3390/ijerph120707457
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Water Quality for Leafy Crops: A Perspective of Risks and Potential Solutions

Abstract: There is increasing evidence of the contribution of irrigation water in the contamination of produce leading to subsequent outbreaks of foodborne illness. This is a particular risk in the production of leafy vegetables that will be eaten raw without cooking. Retailers selling leafy vegetables are increasingly targeting zero-risk production systems and the associated requirements for irrigation water quality have become more stringent in regulations and quality assurance schemes (QAS) followed by growers. Growe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 55 publications
1
118
0
5
Order By: Relevance
“…Notwithstanding this gap in knowledge, irrigation water has long been regarded as an important vehicle for pathogens associated with foodborne illnesses (Uyttendaele et al, 2015). According to the Centers for Disease Control and Prevention, outbreaks that occurred during 2013 to 2014 from drinking water systems solely supplied by surface water accounted for nearly 80% of reported cases (Allende and Monaghan, 2015; Benedict et al, 2017; Uyttendaele et al, 2015). However, there is a paucity of research capable of linking microbial contamination in irrigation water to foodborne outbreaks in the United States (Pachepsky et al, 2016; Partyka et al, 2018).…”
mentioning
confidence: 99%
“…Notwithstanding this gap in knowledge, irrigation water has long been regarded as an important vehicle for pathogens associated with foodborne illnesses (Uyttendaele et al, 2015). According to the Centers for Disease Control and Prevention, outbreaks that occurred during 2013 to 2014 from drinking water systems solely supplied by surface water accounted for nearly 80% of reported cases (Allende and Monaghan, 2015; Benedict et al, 2017; Uyttendaele et al, 2015). However, there is a paucity of research capable of linking microbial contamination in irrigation water to foodborne outbreaks in the United States (Pachepsky et al, 2016; Partyka et al, 2018).…”
mentioning
confidence: 99%
“…The presence of such pathogens could be transmitted to leafy green vegetables when RHRW is used for irrigation purposes. Several studies have linked irrigation water with pathogens isolated from fresh produce (Allende & Monaghan 2015;Gelting et al 2015), therefore substandard irrigation water is a contamination risk factor of fresh green leafy vegetables. The presence of human pathogens on irrigated crops due to the use of contaminated irrigation water is well described (Pachepsky et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the role of irrigation water in the contamination of produce subsequently leading to foodborne illness outbreaks are increasing (Allende & Monaghan 2015). The transfer of any pathogen in water used for irrigation on to crops could be risky if produce is consumed fresh.…”
Section: Stated Thatmentioning
confidence: 99%
“…; De Oliveira Pereira et al., ; Espinosa, Arias, Sánchez‐Colón, & Mazari‐Hiriart, ; Ndiaye, Diop, & Diop, ). Elsewhere, some studies have shown that EV can be transferred onto the surface of vegetables through spray irrigation water resulting in viral contamination of the vegetables (Allende & Monaghan, ; Cheong et al., ; Pachepsky, Shelton, McLain, Patel, & Mandrell, ; Uyttendaele et al., ).…”
Section: Introductionmentioning
confidence: 99%